Bentonite incorporated with granite tailings applied in iron ore pelletizing (Research, Society and Development, 2022)
Numerous factors have contributed to the increase in waste production in large industries, among them steel and mining companies stand out due to their significant environmental impact, such as the pollution of terrestrial and aquatic environments, which has a direct influence on the reduction of the quality of life of local living beings. In this sense, this work investigated the feasibility of incorporating residues from the ornamental rock industry (known as abrasive sludge or RRO) in bentonite clay, aiming to achieve a viable technological route for use in the pelletizing of iron ore. The adopted methodology consisted of the chemical and physicochemical characterization of bentonite in its original state and the incorporation of ornamental rock tailings into bentonite by the following analyses: FRX, DRX, pH, moisture, apparent and absolute density. Subsequently, a statistical analysis of the ideal percentage of incorporation was carried out using the central composite rotational design method. The studied developments were evaluated based on the parameters adopted by Companhia Vale do Rio Doce (CVRD). From the FRX and XRD data, the samples were classified as silico-aluminous, adding more than 70% Si2O + Al2O3 and exhibiting a significant presence of quartz. The compositions that best met the value required by CVRD in relation to pH were four B20 samples, satisfying the basicity condition equal to at least 9.5. For bulk density, B30 presented 940.70 kg.m-3, a value close to the expected (961.20 kg.m-3), whereas for absolute density, two B20 samples showed better results: 2.55 and 2.58 for a benchmark of 2.4 to 2.5.